COVID-19 and social distancing: Disparities in mobility adaptation between income groups. (June 2021) - Iio, Kentaro; Guo, Xiaoyu; Kong, Xiaoqiang; Rees, Kelly; Bruce Wang, Xiubin
Graphical abstract: Highlights: We investigated mobility in Greater Houston by income during the COVID-19 pandemic. Spatially disaggregated mobility data in April 2020 and a baseline were analyzed. Higher income was associated with larger mobility reduction in multiple measures. A need for addressing inequity in urban mobility during the epidemic was apparent. Abstract: In response to the coronavirus disease 2019 (COVID-19) pandemic, governments have encouraged and ordered citizens to practice social distancing, particularly by working and studying at home. Intuitively, only a subset of people have the ability to practice remote work. However, there has been little research on the disparity of mobility adaptation across different income groups in US cities during the pandemic. The authors worked to fill this gap by quantifying the impacts of the pandemic on human mobility by income in Greater Houston, Texas. We determined human mobility using pseudonymized, spatially disaggregated cell phone location data. A longitudinal study across estimated income groups was conducted by measuring the total travel distance, radius of gyration, number of visited locations, and per-trip distance in April 2020 compared to the data in a baseline. An apparent disparity in mobility was found across estimated income groups. In particular, there was a strong negative correlation (ρ = −0.90) between a traveler's estimated income and travel distance in April. Disparities in mobility adaptability were further shown since those in higher income brackets experienced larger percentage drops in the radius of gyration and the number of distinct visited locations than did those in lower income brackets. The findings of this study suggest a need to understand the reasons behind the mobility inflexibility among low-income populations during the pandemic. The study illuminates an equity issue which may be of interest to policy makers and researchers alike in the wake of an epidemic.